Talking to Listeners: Clandestine Audiences in the Early Cold War. Issue 4 (2nd October 2019) - Kind-Kovács, Friederike
Abstract : As 'classical' radio monitoring was—due to massive censorship—only of limited value for gathering uncensored information on Central and Eastern Europe, Radio Free Europe (RFE) relied in the early Cold War extensively on uncensored information brought out by émigrés. RFE interviewed fresh escapees not only to gain knowledge on everyday life but to also collect information on the practice and persecution of clandestine radio listening behind the Iron Curtain. Through the lens of RFE listeners' testimonies and audience reports from the early 1950s, this article explores interviewing as an unorthodox method for gathering information about its own clandestine audiences in the target countries. It uses the Western gaze of individual defectors to better understand how highly subjective stories of clandestine listening were captured, narratively framed and employed in the ideological battle between East and West.